Protex—A Python utility for proton exchange in molecular dynamics simulations - Joerg, Florian; Wieder, Marcus; Schröder, Christian (Frontiers in Chemistry, 2023)
Protex is an open-source program that enables proton exchanges of solvent molecules during molecular dynamics simulations. While conventional molecular dynamics simulations do not allow for bond breaking or formation, protex offers an easy-to-use interface to augment these simulations and define multiple proton sites for (de-)protonation using a single topology approach with two different λ-states. Protex was successfully applied to a protic ionic liquid system, where each molecule is prone to (de-)protonation. Transport properties were calculated and compared to experimental values and simulations without proton exchange.